A study of emotional intelligence and demographic characteristics differences among child and family social workers in Malaysia - Habibie Ibrahim; Sally Johnson; Phillip Gilligan (Universiti Malaysia Sabah, 2016)
The general goal of this quantitative study was to establish whether a self-report measure of emotional intelligence (EI) could be used reliably and validly in Malaysia’s context, particularly with child and family social workers. The quantitative study examined the demographic characteristics of the child and family social workers in relation to EI. The first purpose was to investigate the usefulness of the Assessing Emotional Scale (AES) by Schuette et al. (2007) in the Malaysian context. The second purpose was to examine the levels of EI among the Malaysian child and family social workers and then to determine if the levels of EI differ significantly in terms of gender, marital status, age groups, academic background and length of service experience. EI scores and demographic variables were analysed with the child protectors and rehabilitation officers, who are working in Kota Kinabalu, Petaling and Kuala Lumpur. The Independent-Samples t-test and one-way ANOVA were used to compare the means. The overall result suggest high reported levels of EI. Result findings showed that there were no significant differences on EI for demographic factors among the child and family social workers except for the level of education.